2014
DOI: 10.1289/ehp.1206136
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Artery Responses to Ambient Pollution, Temperature, and Humidity in People with Type 2 Diabetes: A Repeated-Measures Study

Abstract: Background: Extreme weather and air pollution are associated with increased cardiovascular risk in people with diabetes.Objectives: In a population with diabetes, we conducted a novel assessment of vascular brachial artery responses both to ambient pollution and to weather (temperature and water vapor pressure, a measure of humidity).Methods: Sixty-four 49- to 85-year-old Boston residents with type 2 diabetes completed up to five study visits (279 repeated measures). Brachial artery diameter (BAD) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…The mean temperature (11.2 1C (SD 6.6)) during the study period was lower compared to our study (Nawrot et al, 2005). Zanobetti et al 2014 reported a linear relationship of temperature and brachial artery diameter, but observed no association between temperature and FMD or NTGMD (Zanobetti et al, 2014). However, all the results show that even if people are exposed to temperature changes for a short period of time, since people generally spent most of their time indoors; their body reacts to that environmental stimuli.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The mean temperature (11.2 1C (SD 6.6)) during the study period was lower compared to our study (Nawrot et al, 2005). Zanobetti et al 2014 reported a linear relationship of temperature and brachial artery diameter, but observed no association between temperature and FMD or NTGMD (Zanobetti et al, 2014). However, all the results show that even if people are exposed to temperature changes for a short period of time, since people generally spent most of their time indoors; their body reacts to that environmental stimuli.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies have reported an association between air pollution and endothelial dysfunction (Briet et al, 2007;Brook, 2002;Hashemi et al, 2012;O'Neill et al, 2005;Schneider et al, 2008). However, only a few studies have examined the impact of air temperature on endothelial function (Nawrot et al, 2005;Widlansky et al, 2007;Zanobetti et al, 2014), and little is known about the interaction between air temperature and air pollution (Burkart et al, 2013;Roberts, 2004;Stafoggia et al, 2008). Flow-mediated dilatation (FMD) of the brachial artery -quantified as the percent change in diameter induced by reactive hyperemia -is a marker of endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…Assessed as an overall effect, this change in brachial artery caliber is similar to that observed in a previous study by our group (7), which found an average 0.11-mm decrease in BAd 30 minutes after exposure to DE at 200 mg/m 3 . This finding adds to the growing body of literature confirming that acute exposure to traffic-related air pollutants has a consistent and measurable effect on vasocontractility (7,(14)(15)(16)(17)(18) associated with a simultaneous rise in systemic blood pressure (9,19). Interestingly, in this study, we found evidence that both genetic variations and AO supplementation may alter individual susceptibility to the DE exposure.…”
Section: Discussionsupporting
confidence: 75%
“…Exposure to hot weather may induce changes in apparent glucose tolerance (Akanji and Oputa, 1991;Moses et al, 1997), which was most likely due to redistribution of blood flow between visceral beds and the cutaneous (Forst et al, 2006;Zanobetti et al, 2014), and increases in insulin absorption (Koivisto et al, 1981). However, the biological mechanism of cold effects on diabetes mortality remains unclear.…”
Section: Discussionmentioning
confidence: 99%